2019
DOI: 10.5455/javar.2019.f313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Inorganic and Three Forms of Organic Trace Minerals on Growth Performance, Carcass Traits, Immunity and Profitability of Broilers

Abstract: Objective: The experiment was conducted to investigate the comparative effects of inorganic trace minerals (ITM) and three forms of organic trace minerals (OTM) (propionate, metho-chelated, and proteinate) on growth performance, edible meat yield, immunity, and profitability of commercial broilers. Materials and methods: A corn-soya based mash diet comprising four treatments each of 10 replicates were fed to 720 day-old Cobb 500 broiler chicks for 35 days (starter diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Increased levels of minerals like zinc along with phytase in diets of poultry lead to better utilization of nutrients and enhance production performances (Akter et al 2017). Organic forms of minerals have numerous advantages over the inorganic forms, for example, proteinate and propionate organic trace minerals were found to be more effective in improving performance, immune response, and profitability in broiler birds than inorganic trace minerals (Khatun et al 2019). They may affect bioavailability and hence tissue levels thereby determining the actual concentration at sites of requirement or action.…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of minerals like zinc along with phytase in diets of poultry lead to better utilization of nutrients and enhance production performances (Akter et al 2017). Organic forms of minerals have numerous advantages over the inorganic forms, for example, proteinate and propionate organic trace minerals were found to be more effective in improving performance, immune response, and profitability in broiler birds than inorganic trace minerals (Khatun et al 2019). They may affect bioavailability and hence tissue levels thereby determining the actual concentration at sites of requirement or action.…”
Section: Advances In Delivery Of Nutraceuticalsmentioning
confidence: 99%
“…Nutraceuticals have been in focus in poultry science quite recently due to the nutritional and healthier properties of feed ingredients and the adverse effects of chemical pharmaceuticals like antibiotic resistance and drug residues (Elnesr et al 2019a(Elnesr et al , 2020. Amino acids (Ghoreyshi et al 2019), minerals (Khatun et al 2019), and vitamins (Ahmad et al 2019) which are common ingredients of poultry ration or a combination of them (Moghaddam & Emadi 2014; Horvath & Babinsky 2018) can be nutraceuticals, especially important in poultry feeding. Generally, poultry receives nutrients through the consumption of natural feedstuffs, but some key essential amino acids (lysine, methionine, threonine and tryptophan), vitamins and minerals are often offered as synthetic supplements (Ravindran 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Minerals used in poultry diets mostly consist of an inorganic form ( Van der Klis et al., 2002 ; Vieira, 2008 ). However, minerals can also be processed and bound to for example, an amino acid or a protein ( Khatun et al., 2019 ; Wang et al., 2019 ) and are then called organic minerals. Organic macro and trace minerals in broiler's diet ( Huang et al., 2009 ; Zhao et al., 2010 ) and organic trace minerals in broiler breeders’ diet ( Bao and Choct, 2009 ; Swiatkiewicz et al., 2014 ; Torres and Korver, 2018 ) have been shown to have a higher bioavailability than inorganic minerals, due to a higher chemical stability and consequently a better intestinal absorption ( Wedeking et al., 1991 ; Bao and Choct, 2009 ; Wang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mineral elements in human, animal and plant nutrition has been well recognized (Underwood, 1971). Khatun et al, (2018) reported that two forms of organic trace minerals such as propionate and proteinate improved performance of commercial broilers over those of in-organic trace minerals. Every form of living matter requires these inorganic elements or minerals for their normal life processes (Hays and Swenson, 1985;Ozcan, 2003).…”
Section: Introductionmentioning
confidence: 99%